"You Just Have to Keep Going, You Can't Give Up": Coping mechanisms among young adults with lupus transferring to adult care. (December 2021) - Bitencourt, Nicole; Ciosek, Ashley; Kramer, Justin; Solow, E Blair; Bermas, Bonnie; Wright, Tracey; Nassi, Lorien; Makris, Una
Introduction: Coping mechanisms and emotional regulation are important contributors to psychosocial health during stressful life events. We sought to describe the coping and emotional responses of persons with childhood-onset systemic lupus erythematosus during the transfer from pediatric to adult healthcare. Methods: Semi-structured in-depth one-on-one interviews were conducted with 13 young women aged 18–24 of minority background who had transferred to adult care in a public hospital system. Thematic analysis was used to identify themes motifs from the data. Results: Participants described the use of (1) problem-focused coping such as the use of clear communication and self-education, (2) adaptive emotion-focused coping such as cognitive reframing and acceptance, (3) social coping including support-seeking, (4) meaning-making coping including positive religious framing and viewing events as learning opportunities for growth, and (5) disengaged coping including denial and social isolation. A range of emotional responses associated with the transfer were described including fear, anger, loss, and feelings of empowerment and excitement. Conclusion: Effective coping and emotional regulation are modifiable factors that may impact transfer-related outcomes and psychosocial health. Addressing coping mechanisms is relevant to the optimized transfer to adult care.